การพัฒนาเกษตรกรรายย่อยแบบมีส่วนร่วมในการผลิตปาล์มน้ำมัน อย่างยั่งยืน: กรณีศึกษาสมาชิกกลุ่มวิสาหกิจชุมชนเทพพิทักษ์ปาล์ม จังหวัดตรัง - ทองรักษ์ สุธัญญา; เกียรติปฐมชัย สิริรัตน์; จันทรนิยม ธีระพงศ์ (Area Based Development Research Journal, 2018)
This research aims to develop the smallholders towards sustainable oil palm production through group process in Thailand. The study attempts to solve the fundamental problems of smallholders in oil palm production through sharing knowledge, and encouraging them to adopt sustainable oil palm management practices (SMP). The study emphasizes on public, private and smallholders’ participation (Agri-PPPs). This study carried out several important activities such as selecting the palm oil crushing mill and smallholders, creating the farmers’ group, setting up the group administration according to RSPO (Roundtable on Sustainable Palm Oil) standard, preparing training materials, arranging training and excursion, monitoring and evaluation. Data were collected from a total of the 101 members in the farmer group. Statistical tools such as descriptive statistics and t-test were employed. The findings showed that most of the smallholder’s problems in oil palm production could be solved by the group’s process and with the support of the palm oil crushing mill and the research project. It was also found that after obtaining appropriate knowledge of SMP, the smallholders considerably changed their practices in oil palm production, particularly in adjusting oil palm plantation management, recording the farm data, improving the application of chemical fertilizer by using strength fertilizers, stopping and reducing chemicals uses. As a result, the farmers’ productivity in oil palm production increased as well as the environmental quality improved. The smallholders were also satisfied being members of the group. In addition, the farmers’ group acted as a center for sharing knowledge and experience. Therefore, the smallholders themselves can solve their problems in oil palm production. More importantly, they have learned and realized the power of working as a group. In addition, the partner crushing mill obtained target quantity and quality of oil palm fresh fruit brunches. Findings of the study might be applied to the development of other smallholders through group process in order to ensure sustainability in oil palm production all over country.